Field Assessment for Initial Preparation of Net Zero Building Certification for The Universitas Multimedia Nusantara (UMN) Building: A Case Study On Visual Comfort in C and D Tower - Pranata, Nicholas; Salehuddin, Muhammad (Ultima Computing : Jurnal Sistem Komputer, 2024)
Ensuring optimal physical comfort, the need for a comprehensive evaluation of the performance of building systems was established. This investigation endeavors to meticulously scrutinize illuminance and light power density metrics across distinct temporal segments (morning, noon, afternoon, and night), as well as the dynamism of daylighting and artificial lighting presence within Tower C and D of Universitas Multimedia Nusantara (UMN). Noteworthy for their incorporation of double skin façades, these edifices serve as focal points of inquiry. The empirical findings reveal that illuminance levels within classrooms and offices, irrespective of natural or artificial lighting, consistently fall short of the prescribed 350 lux threshold based on SNI across most floor levels. The efficacy of the double skin façade manifests in a discernible attenuation, diminishing illuminance ingress to the building by approximately 50%, and precipitously by up to 90% about window fixtures. Furthermore, the analysis of light power density underscores an energy efficiency quotient hovering around 60%. These empirical insights are intended to serve as a foundational resource for guiding the initiation of Net Zero Healthy Greenship certification endeavors.